5(h+1)+3(h-2)=12

Simple and best practice solution for 5(h+1)+3(h-2)=12 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(h+1)+3(h-2)=12 equation:


5(h+1)+3(h-2)=12

We simplify the equation to the form, which is simple to understand
5(h+1)+3(h-2)=12

Reorder the terms in parentheses
+(+5h+5)+3*(h-2)=12

Remove unnecessary parentheses
+5h+5+3+*(+h-2+)=+12

Reorder the terms in parentheses
+5h+5+(+3h-6)=12

Remove unnecessary parentheses
+5h+5+3h-6=+12

We move all terms containing h to the left and all other terms to the right.
+5h+3h=+12-5+6

We simplify left and right side of the equation.
+8h=+13

We divide both sides of the equation by 8 to get h.
h=1.625

See similar equations:

| (x^3-2x^2)+1=0 | | y^2*(120-y)=1.25 | | 8x+3x=32 | | 7x+3x=-1 | | 120y^2-y^3=1.25 | | 3x+20x=200 | | 9x+2x=105 | | 4x+3x=92 | | ln(x/6)=-6 | | 100=80+x | | 0.25b+0.50=13.75 | | 484=4*5.5 | | 4x=9+7 | | 2y^2-6y-9=0 | | y=-3.310log(X)+29.82 | | 3x+4x+5x=3840 | | X^2+2xifX=-2 | | 4x-1=6x-4 | | X^2+2xwhenX=-2 | | x-33=3x-699 | | x/4-2=250 | | x=5a+2*(3-a)-6 | | 12*n+1*(2n+2)=100 | | 12*n+1*(2n+2)=43 | | 8-9=x | | 12*n+1*(2n+2)=436 | | 5x-8=102 | | 99.3(.7)+x(.3)=95 | | Y=2px+y^2+p^3 | | 5x^3+2x^2+10x+4=0 | | 4a+5b=40 | | u^4-14u^2+40=0 |

Equations solver categories